2013
DOI: 10.1128/jcm.01730-13
|View full text |Cite
|
Sign up to set email alerts
|

First Outbreak of KPC-2-Producing Klebsiella pneumoniae Sequence Type 258 in a Hospital in South Korea

Abstract: fIn this study, we report the first outbreak of KPC-2-producing Klebsiella pneumoniae isolates from three patients admitted to a neurosurgery department in a South Korean teaching hospital. Multilocus sequence typing showed that the isolates were identical to the previous KPC producers in South Korea and other countries, suggesting clonal spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…Therefore, the wide spread of the producers is one of the worrisome global issues encountering antimicrobial resistance. In accordance of occasional reports (Rhee et al, 2010 ; Hong et al, 2013 ; Yoo et al, 2013 ) and data from NLSS (unpublished data), only infrequent occurrence of the KPC producers were identified in South Korea until 2013. However, after a sudden expansion of KPC producers in 2014, rapid nation-wide spread supported by single-hospital outbreaks (Kim et al, 2017 ), frequently associated with inter-hospital or inter-regional spread (Jeong et al, 2016 ) led the endemic stage of KPC in 2015.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, the wide spread of the producers is one of the worrisome global issues encountering antimicrobial resistance. In accordance of occasional reports (Rhee et al, 2010 ; Hong et al, 2013 ; Yoo et al, 2013 ) and data from NLSS (unpublished data), only infrequent occurrence of the KPC producers were identified in South Korea until 2013. However, after a sudden expansion of KPC producers in 2014, rapid nation-wide spread supported by single-hospital outbreaks (Kim et al, 2017 ), frequently associated with inter-hospital or inter-regional spread (Jeong et al, 2016 ) led the endemic stage of KPC in 2015.…”
Section: Discussionsupporting
confidence: 77%
“…The carbapenem resistance of the isolate that we uncovered in this study may not be due to the horizontal transfer of the plasmid and clonal spread because similar plasmids carrying bla KPC-2 have not been reported and because the K. pneumoniae isolate carrying pKPC-DK05 has a novel genotype unknown to produce K. pneumoniae carbapenemase (KPC) (5)(6)(7)(8). Thus, we can speculate that our carbapenemase-producing K. pneumoniae isolate emerged via incorporation of Tn4401 into the prevailing plasmid.…”
mentioning
confidence: 81%
“…From 1990 to 2015, there were many studies that reported the identification of the first cases of KPC-producing K. pneumoniae isolates in different countries such as USA, Canada, Italy, Poland, France, Spain, UK, Colombia, India, Argentina, China, Ireland, Greece, Brazil, Turkey, Japan, South Korea, and Iran 9, 10, 11, 12, 13, 14, 15, 16, 17. KPC-producing K. oxytoca isolates are rarely reported [18].…”
Section: Introductionmentioning
confidence: 99%